2024
DOI: 10.1038/s41598-024-60458-z
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the origin, fate, impacts and harm of microplastics and antibiotic resistance genes in wastewater treatment plants

Ke Zhao,
Chengzhi Li,
Fengxiang Li

Abstract: Previous studies reported microplastics (MPs), antibiotics, and antibiotic resistance genes (ARGs) in wastewater treatment plants (WWTPs). There is still a lack of research progress on the origin, fate, impact and hazards of MPs and ARGs in WWTPs. This paper fills a gap in this regard. In our search, we used “microplastics”, “antibiotic resistance genes”, and “wastewater treatment plant” as topic terms in Web of Science, checking the returned results for relevance by examining paper titles and abstracts. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 165 publications
0
0
0
Order By: Relevance
“…Since high-MP ponds are close to human activity hubs, they are at greater risk of antibiotic contamination through sewage runoff. Furthermore, the increase of ARGs within host microbiomes in high-MP ponds supports the hypothesis that MP may provide a route for human-derived antibiotics and ARGs to enter and establish within aquatic host microbiomes (Zhao et al, 2024; Chaturvedi et al, 2023). Interestingly, we found that the host microbiome community from a high-MP environment was enriched in genes encoding PET catabolism.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Since high-MP ponds are close to human activity hubs, they are at greater risk of antibiotic contamination through sewage runoff. Furthermore, the increase of ARGs within host microbiomes in high-MP ponds supports the hypothesis that MP may provide a route for human-derived antibiotics and ARGs to enter and establish within aquatic host microbiomes (Zhao et al, 2024; Chaturvedi et al, 2023). Interestingly, we found that the host microbiome community from a high-MP environment was enriched in genes encoding PET catabolism.…”
Section: Discussionsupporting
confidence: 62%
“…With the transfer of these members comes the transfer of some genes associated with microplastics (MP). These include plastic polymer degradation enzymes and antibiotic resistance genes (ARGs), which have been demonstrated to spread via MP-associated biofilms (Kaur et al ., 2022; Zhao et al ., 2024).…”
Section: Introductionmentioning
confidence: 99%